1992
DOI: 10.1007/bf00012802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of legumes on soil physical quality in a maize crop

Abstract: The effect of intercropped legumes and three N fertilizer rates in a continuous maize (Zea mays L.) cropping system on the physical properties of two soils were investigated for three years. The legumes, being a mixture of alfalfa, clover and hairy vetch, had a significant cumulative effect on some physical properties of both soil. The lowest stability and smallest mean weight diameter of soil aggregates were associated with monoculture maize plots. Aggregate size and stability were not affected by N fertiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 13 publications
1
43
0
2
Order By: Relevance
“…As reported here, P additions have been shown to increase soil aggregation (Nobrega et al, 2001;Gil et al, 2009;Alguacil et al, 2010;Ortas and Lal, 2012), but also N additions (Latif et al, 1992;Tripathi et al, 2008;Wilson et al, 2009;Guo et al, 2012) as well as the application of multi-component fertilizers Hati et al, 2006;Huo et al, 2008). As proposed here, many studies focused on the indirect impact of AMF hyphal length and root abundance in this context.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As reported here, P additions have been shown to increase soil aggregation (Nobrega et al, 2001;Gil et al, 2009;Alguacil et al, 2010;Ortas and Lal, 2012), but also N additions (Latif et al, 1992;Tripathi et al, 2008;Wilson et al, 2009;Guo et al, 2012) as well as the application of multi-component fertilizers Hati et al, 2006;Huo et al, 2008). As proposed here, many studies focused on the indirect impact of AMF hyphal length and root abundance in this context.…”
Section: Discussionsupporting
confidence: 56%
“…By contrast, to our knowledge only very few experiments have been conducted in natural systems, covering a limited range of ecosystem types like temperate grasslands (Van Groeningen et al, 2002;Wilson et al, 2009) or dry tropical savanna (Tripathi et al, 2008). The majority of these studies report positive effects of nutrient additions on soil aggregation, often accompanied by increases in root and arbuscular mycorrhizal fungal (AMF) hyphal abundance (Latif et al, 1992;Nobrega et al, 2001;Wilson et al, 2009;Alguacil et al, 2010). The latter are important factors in the process of aggregate formation, though abiotic factors likewise may play an important role: Fertilization studies focusing on abiotic soil parameters also demonstrated interrelations with pH and the proportion of exchangeable cations and electrostatic binding agents Graham et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…During the first period of the experiment, the clover content in the conventional (CS4) and the organic (CS5) leys were 12-24% and 16-63%, respectively (Korsaeth and Eltun, 2000). Favourable effects on soil structure have been reported for several legumes grown together with maize (Latif et al, 1992). On the other hand, Breland (1995) found that ryegrass sown as a catch crop had a better effect on soil structure than did white clover, probably because its roots bound the soil well and provided carbon-rich material that stimulates microbial activity.…”
Section: Soil Structure and Organic Mattermentioning
confidence: 96%
“…In addition to providing adequate cover to reduce soil erosion (Wall et al 1991) and increase soil water infiltration (Bruce et al 1992), legume living mulches improve soil nutrient status through addition of organic nitrogen (N) (Holderbaum et al 1990;Brown et al, 1993) via fixed atmospheric nitrogen which improves soil physical properties (McVay et al 1989;Latif et al 1992). Incorporating legume living mulches can also increase the yield of the succeeding crop (Bollero and Bullock 1994;Decker et al 1994).…”
Section: Introductionmentioning
confidence: 99%